Surface Dielectric Barrier Discharge plasma: a suitable measure against fungal plant pathogens - Ambrico, Paolo F; Šimek, Milan; Rotolo, Caterina; Morano, Massimo; Minafra, Angelantonio; Ambrico, Marianna; Pollastro, Stefania; Gerin, Donato; Faretra, Francesco; De Miccolis Angelini, Rita M (Scientific reports, 2020)
Fungal diseases seriously affect agricultural production and the food industry. Crop protection is usually achieved by synthetic fungicides, therefore more sustainable and innovative technologies are increasingly required. The atmospheric pressure low-temperature plasma is a novel suitable measure. We report on the effect of plasma treatment on phytopathogenic fungi causing quantitative and qualitative losses of products both in the field and postharvest. We focus our attention on the in vitro direct inhibitory effect of non-contact Surface Dielectric Barrier Discharge on conidia germination of Botrytis cinerea, Monilinia fructicola, Aspergillus carbonarius and Alternaria alternata. A few minutes of treatment was required to completely inactivate the fungi on an artificial medium. Morphological analysis of spores by Scanning Electron Microscopy suggests that the main mechanism is plasma etching due to Reactive Oxygen Species or UV radiation. Spectroscopic analysis of plasma generated in humid air gives the hint that the rotational temperature of gas should not play a relevant role being very close to room temperature. In vivo experiments on artificially inoculated cherry fruits demonstrated that inactivation of fungal spores by the direct inhibitory effect of plasma extend their shelf life. Pre-treatment of fruits before inoculation improve the resistance to infections maybe by activating defense responses in plant tissues.
Keywords: mitosporické houby; Spores, Fungal; Mitosporic Fungi; Plasma Gases; plazmové plyny; spory hub; Plant Diseases; nemoci rostlin